Learning Strategies and Communication Styles at SLB Autism YPPA Bukittinggi: Educational Communication for Students with Autism - Minneri, Fadhil Shafar; Lestari, Yayuk; Annindya, Annisa; Tohari, Diyah Rachmawati (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
This study focuses on educational communication in the context of SLB Autisma YPPA Bukittinggi, specifically on teaching strategies and communication styles between teachers and autistic students. The research method involves interviews with the Head of the Special Needs School and an analysis of teaching practices in both classical and therapy classes. The research findings indicate that communication between teachers and autistic students relies on understanding varied communication styles. The therapy class, using the ABA approach, emphasizes individuality and personalized learning. Communication styles in the therapy class are dominated by teachers, who utilize repetition, emphasis, and motivation to achieve learning objectives. Learning strategies that comprehend the uniqueness of each student and utilize cognitive learning theories can aid in achieving optimal learning outcomes.